Genetic differentiation in the genus Characodon: implications for conservation and taxonomy - Rosa G. Beltrán-López; Rodolfo Pérez-Rodríguez; Ofelia C. Montañez-García; Juan M. Artigas-Azas; Michael Köck; Adán F. Mar-Silva; Omar Domínguez-Domínguez (PeerJ, 2021)
The subfamily Goodeinae is a group of fishes endemic to the Mexican highlands. Most of the species are restricted to small and isolated streams or springs. Within this subfamily, the genus Characodon is the earliest diverging lineage of which three species have been described: C. lateralis, C. audax, and C. garmani, with the latter, considered extinct. Characodon lateralis and C. audax are classed as endangered, and have been the subject of taxonomic controversy since their description: previous studies have recognized a genetic differentiation in two groups separated by the El Salto waterfall, but morphological analyses contradict these genetic results. We perform a phylogeographic study using the mitochondrial cytb gene and d-loop region to elucidate the evolutionary history of C. lateralis and C. audax. The results with both markers show the presence of two highly differentiated haplogroups; one distributed north and the other distributed south of the waterfall, with genetic distances of 1.7 and 13.1% with cytb and d-loop respectively, and divergence calculated to have occurred 1.41 Mya. Significant genetic structure was found within each haplogroup and suggests the existence of at least four Evolutionary Significant Units (ESUs) within the examined populations. The possible processes identified as contributing to the formation of differentiated genetic groups are isolation, low population size, recurrent bottlenecks, and the strong sexual selection exhibited by the genus.